UMP students excited to celebrate Eid - Mimi Rabita, Abdul Wahit (UMPSA, 2022)
PAYA BESAR, 23 May 2022 - After two years of not celebrating the festivities of Aidilfitri, the arrival of the month of Syawal this time was awaited with excitement among students.